Euro Area Policies : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation on euro area policies highlights that 10 years after its launch, monetary union is a distinct success and the euro area a zone of stability in the international economy. However, economic union remains work in progress. Improved wage setting and labor market reforms have contributed to the creation of some 16 million jobs over the past decade. Similarly, the single market program and product market reforms have raised productivity in affected sectors. The outlook for financial stability is highly uncertain, although the area's financial system remains sound.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet